The measure of effectiveness of a short-term 2-week intensive Cardiac Rehabilitation program in decreasing levels of anxiety and depression - Floriana Caccamo; Simone Saltini; Enrico Carella; Roberto Carlon; Cristina Marogna; Vito Sava (Monaldi Archives for Chest Disease, 2018)
Research on heart disease have found a strong and consistent evidence of association between some psychosocial risk factors, including depression, anxiety, self-efficacy, lack of social support and outcome of disease. Depression increases the risk of cardiac death and is highly predictive of reduced adherence to recommended treatments; anxiety appears to be linked to adverse cardiac outcomes. It was demonstrated that Cardiac Rehabilitation (CR) leads to substantial improvements and positive outcomes because combines the prescription of physical activity with the modification of risk factors and aims to reduce symptoms related to the disease and the risk of new cardiovascular events. The main objective of this study is to determine if a short and intense CR program can produce a positive impact on anxious and depressive symptoms revealed in cardiac patients, confirming results of previous researches. The protocol was proposed to all patients referred for an outpatient CR after an acute event who attended the short 2-week intensive rehabilitation program. A total of 157 patients recruited at the operating unit of Cardiology, in the Hospital of Cittadella (Italy), was included in the analysis. The Beck Depression Inventory-II and the State-Trait Anxiety Inventory-Y were administered to the patients. SPSS 17.0 was used for statistical analysis. T-tests for paired samples were used to evaluate differences between the beginning and the end of the CR program. There was a statistically significant difference between the beginning and the end of the CR program. Results for paired samples showed significant differences in all factors of the BDI-II and in the total score. In addition, a statistically significant difference was found even in the state - anxiety subscale. No significant difference was detected for the trait anxiety. According to recent studies, this research shows that the CR program has a significant impact on levels of anxiety and depression, because all activities focus their commitment on changing the patient’s personal beliefs and perception of illness, promoting the exchange of information and sharing of concerns and fears, increasing the patient’s resilience with the aim of enabling him/her to reorganize positively his/her personal, family and professional sphere.